Pengembangan Media Pembelajaran Teka-Teki Matematika Untuk Meningkatkan Pemahaman Konsep Matematis Siswa Pada Materi Perbandingan - Musyafak, Musyafak; Kusmaryono, Imam; Basir, Mochamad Abdul (Jurnal Pendidikan Sultan Agung, 2024)
Mathematical puzzles are learning media based on Android applications that aim to improve students' understanding of mathematical concepts, especially in comparative material. The development of this application is based on the teacher's lack of innovation in making learning media. The purpose of this application is to make new innovations related to the development of learning media called Mathematical Puzzles which are valid, practical, and effective for increasing students' understanding of mathematical concepts in comparative material. This type of research is research and development (Reasearch and Development). The subjects of this study were students of class VII MTs Nahdlatul Ulama Tengguli Jepara. The development model applied is the development model in this study, namely ADDIE. The data collection techniques applied in this study were product validation questionnaires, teacher and student practicality response questionnaires, student mathematical ability test questions, and student motivation questionnaires. The data analysis applied was media expert and material expert tests, practicality tests through teacher and student response questionnaires, and effectiveness tests through classical tests and influence tests. The results of this study indicate that the learning media for math puzzles to improve understanding of mathematical concepts meets valid criteria with a validity value of 3.27, practical with a practicality value of 3.56, and is effective with a classical completeness test score of 80% and an effect test with influential results.